Consumo alimentar e perfil nutricional de discentes de uma universidade federal no Médio Solimões - (:unkn) unknown (ISB - Instituto de Saúde e Biotecnologia (Coari), 2026)
Assessing the food consumption of the Amazonian population is a major challenge, given the cultural diversity and the limited access to certain foods. Objective: To evaluate the food consumption and nutritional profile of patients treated at the outpatient clinic of a federal university located in the Middle Solimões region, Amazonas. Methods: This is a cross-sectional, analytical study, approved under CAEE No. 08021319.0.0000.5020. Students and staff treated at the outpatient clinic of the Teaching Clinic were evaluated. Sociodemographic data were collected through a semi-structured questionnaire. Food consumption through the Food Frequency Questionnaire (FFQ) and anthropometric assessment (weight, height, Body Mass Index (BMI), skin folds and circumferences). The data obtained were organized and analyzed using a Microsoft Excel® spreadsheet, version 10. Results: 21 patients were evaluated, of which 28.57% (6) were male and 71.43% (15) were female. The salary income of 52.38% (11) of those assessed was one to two minimum wages per month. Regarding the nutritional diagnosis, 52.38% (11) of those evaluated were eutrophic according to BMI; 47.62% (10) had a high fat percentage and 61.90% (13) had an adequate percentage of arm muscle circumference. Men were more physically active, did not smoke and were more hydrated when compared to women. Food consumption showed daily consumption of French bread and instant noodles. Conclusion: The analysis of food consumption reveals a dual scenario: while traditional habits are preserved, there is a gradual introduction of processed foods into the daily lives of young university students, which characterizes a possible dietary transition.
Keywords: Alimentos processados; Estado nutricional; Transição nutricional; CIENCIAS DA SAUDE: NUTRICAO; Avaliação nutricional; Hábitos alimentares; Estudantes universitários - Nutrição